2014
DOI: 10.1002/chem.201404633
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of Multisubstituted Isoquinolines from Pyridines by Regioselective Diels–Alder Reactions of 2‐Silyl‐3,4‐pyridynes

Abstract: A four-step regioselective synthesis of multisubstituted isoquinoline derivatives from 3-bromopyridines was developed by the Diels-Alder (DA) reactions of 2-silyl-3,4-pyridynes with furans, followed by functional-group transformations. In particular, the silyl group at the C2-position of the 3,4-pyridynes played two important roles: firstly, it functioned as the directing group for the DA reaction, and secondly, it served to introduce diverse substituents at the C1-position of the isoquinolines by electrophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A few examples of silylaryl halide use in aryne generation have been reported . In 1973, Cunico and Dexheimer reported that (2-halophenyl)- and [2-(tosyloxy)­phenyl]­trimethylsilanes are capable of generating arynes in the presence of KO- t -Bu or fluoride ion .…”
mentioning
confidence: 99%
“…A few examples of silylaryl halide use in aryne generation have been reported . In 1973, Cunico and Dexheimer reported that (2-halophenyl)- and [2-(tosyloxy)­phenyl]­trimethylsilanes are capable of generating arynes in the presence of KO- t -Bu or fluoride ion .…”
mentioning
confidence: 99%
“…In these cases, the reactive sites of the benzynes were completely controlled by the electron-withdrawing and electron-donating inductive effects of the C3-alkoxy and C3-boryl group, respectively. [68][69][70][71][72][73][74][75][76][77][78] The fluorination of 3-(tert-butyldimethylsilyl) benzyne 4f gave a mixture of meta-1f and ortho-1f in a 6.4 : 1 ratio under both batch and flow conditions (Entry 5). In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f.…”
Section: Resultsmentioning
confidence: 99%